1988
DOI: 10.1128/mcb.8.9.3857
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid and developmental regulation of amylase mRNAs in mouse liver cells.

Abstract: We characterized alpha-amylase expression in the hepatoma cell line Hepa 1-6 and in normal mouse liver. Both Amy-1 and Amy-2 were expressed in Hepa 1-6 and were regulated by glucocorticoids. Transcription in the hepatoma cells was initiated at the same start sites as in mouse tissues. Glucocorticoid treatment increased the abundance of Amy-1 and Amy-2 transcripts by 10 to 20-fold. This increase was detected within 4 h and was maximal by 24 h. The pattern of amylase expression in this hepatoma cell line accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…ME13 containing the mouse elastase cDNA sequences (bp +830 to +1105) in pGEM-1 was a gift from Raymond MacDonald. Amy2 riboprobe was a construct that contained the 5' end (bp -516 to +115) of the Amy 2.2 gene in pGEM-2, as described previously (40).…”
Section: Methodsmentioning
confidence: 99%
“…ME13 containing the mouse elastase cDNA sequences (bp +830 to +1105) in pGEM-1 was a gift from Raymond MacDonald. Amy2 riboprobe was a construct that contained the 5' end (bp -516 to +115) of the Amy 2.2 gene in pGEM-2, as described previously (40).…”
Section: Methodsmentioning
confidence: 99%
“…In humans, the amylase gene family is composed of five genes (AMY1A, AMY1B, AMY1C, AMY2A and AMY2B) which were generated during primate evolution from one ancestral gene copy (Samuelson et al 1990). AMY2B is the only one of the five gene members that does not have a retroviral insertion site, which likely affects transcription (Samuelson et al 1988a, b; Yokouchi et al 1990), and suggests that it is an older version of the gene (Samuelson et al 1990). Amylase 1 (AMY1) is produced in the salivary glands, and AMY1 CNVs have been identified in different human populations that correlate with starch intake in those geographic regions (Perry et al 2007; Mandel et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This control of the synthesis of pancreatic proteins might be exerted by a number of hormones such as corticosterone and thyroxine, the concentrations of which increase during the second and third postnatal weeks (Henning, 1987). During normal development, the level of amylase parallels that of corticosterone in the rat serum (Takeuchi et al 1977), and glucocorticoids were found to induce the transcription of amylase gene in both hepatoma cells (Samuelson et al 1988) and the AR4-2J cell line (Logsdon et al 1987). A DNA sequence able to interact with the glucocorticoid receptor has been located in the promoter region of both amylase 1 and 2 genes (Osborn et al 1987).…”
Section: Postnatal Developmentmentioning
confidence: 99%